Post-Transcriptional Dysregulation of microRNA and Alternative Polyadenylation in Colorectal Cancer - Mao, Zhanrui; Zhao, Hui; Qin, Yulan; Wei, Jianming; Sun, Jielin; Zhang, Weiwei; Kang, Yani (Frontiers in Genetics, 2020)
Background: Colorectal cancer (CRC) is one of the leading causes of cancer death worldwide. MicroRNAs (miRNAs) repress gene expression by binding to complementary sequences in the 3’ untranslated region (3’UTR) of target mRNAs. Alternative polyadenylation (APA) are relevant to the variability of the 3’UTR of mRNA. However, the post-transcriptional dysregulation of miRNAs and APA in CRC are poorly understood. Method: In this study, we conducted small RNA sequencing to identify differentially expressed miRNAs (DERs) and their target genes. Function analysis on DER-target genes can explain the regulation roles of miRNAs in CRC. The mutual regulation of miRNAs and APA was analyzed by combining miRNA data to 3’UTR alteration using 3’ termini of polyadenylated RNAs sequencing (3T-seq) technique, and this was validated using TCGA gene expression data. Results: Our results showed 64 significant differentially expressed miRNAs (DERs) in CRC patients. Their target genes were related to cell adhesion and transcription regulation and were prevailingly involved in the CRC-related pathway. Integrative analysis of the miRNA and APA profile revealed 16 DERs targeting 12 polyadenylation factors, and six of them were significantly differently expressed in CRC. We also found four DERs that lost binding sites due to APA and showed a positive correlation between the miRNA and gene expression. Conclusion: Our study found that miRNAs regulated APA by modulating key polyadenylation factors, and several miRNAs lost their suppression on mRNA due to APA. Associating this with gene expression may provide some important clues for a deeper study of post-transcriptional cellular regulation and biomarker research in CRC. Our data provided the first evidence that the interaction between miRNAs and APA associated with gene expression could serve as biomarkers for CRC, suggesting that hsa-miR-133a-3p and MLEC, hsa-miR-145-5p and SET, hsa-miR-1-3p and PPIA, and hsa-miR-378d and YY1 might be novel and potential biomarkers in improving the diagnosis of CRC.